2012
DOI: 10.3390/s120912329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Thickness of the Sensitive Layer on the Performance of the Accumulating NOx Sensor

Abstract: A novel and promising method to measure low levels of NOx utilizes the accumulating sensor principle. During an integration cycle, incoming NOx molecules are stored in a sensitive layer based on an automotive lean NOx trap (LNT) material that changes its electrical resistivity proportional to the amount of stored NOx, making the sensor suitable for long-term detection of low levels of NOx. In this study, the influence of the thickness of the sensitive layer, prepared by multiple screen-printing, is investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Groß et al demonstrated the dependency of the dosimeter-type NO x sensing properties on the thickness of the carbonate-based sorbent. Since nitrates form mainly at the surface of the sorbent, the sensitivity of the NO x accumulating sensor decreases with a growing layer thickness as the linear measurement range increases (Groß et al, 2012b). Additionally, the sensor response time concerning the concentration detecting properties was found to increase with the layer thickness.…”
Section: Influencing Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Groß et al demonstrated the dependency of the dosimeter-type NO x sensing properties on the thickness of the carbonate-based sorbent. Since nitrates form mainly at the surface of the sorbent, the sensitivity of the NO x accumulating sensor decreases with a growing layer thickness as the linear measurement range increases (Groß et al, 2012b). Additionally, the sensor response time concerning the concentration detecting properties was found to increase with the layer thickness.…”
Section: Influencing Factorsmentioning
confidence: 91%
“…7b, whereas it is even 18.5 h for the annual value of 40 µg m −3 . Besides the sensitivity, the linear measurement range of the presented sensor was found to be affected by temperature as well as by the thickness (Groß et al, 2012b) of the sensitive layer. The linear range always ends at a sensor response change of about 30 to 40 %.…”
Section: Examples For Conductometric Gas Dosimetersmentioning
confidence: 99%
See 1 more Smart Citation
“…During the NO x loading stage, Δ R rel is expected to increase in the presence of NO x at T sorption due to progressive NO x accumulation, without recovery (Figure 4(a)). In the case of a constant flow rate, the cumulated NO x exposure (or dose) A NOx,in is given by the time integral of c NOx,in as sketched in Figure 4(b), resulting in the unit ppm·s [6,16,37]. …”
Section: Nox Sensing Propertiesmentioning
confidence: 99%
“…Small deviations of the NO 2 related data points from linearity at the initial stage of exposure may originate from NO 2 adsorption on the inner surface of the feed lines. The sensing characteristics and in particularly the sensitivity of NO x dosimeter with a comparable sensitive material were found to be dependent on the temperature as well as on the thickness of the sensitive layer [6,16]. …”
Section: Nox Sensing Propertiesmentioning
confidence: 99%